2016
DOI: 10.1161/strokeaha.115.012520
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Upper Extremity Robotic Therapy in Subacute Poststroke Hemiplegia

Abstract: Background and Purpose— Our aim was to study the efficacy of robotic therapy as an adjuvant to standard therapy during poststroke rehabilitation. Methods— Prospective, open, blinded end point, randomized, multicenter exploratory clinical trial in Japan of 60 individuals with mild to moderate hemiplegia 4 to 8 weeks post stroke randomized to receive standard therapy plus 40 minutes of either robotic or self-guided therapy for 6 weeks (7 days/week). Upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 7 publications
1
67
0
2
Order By: Relevance
“…Using the minimal clinically important difference (MCID) as a reference, the mean difference between the patients in the RT and control groups with respect to the FMA upper-limb score is expected to be 4.25 points (30). Given that the subjects in this study will be chronic patients, the deviation is expected to be smaller than that in the pilot study conducted in recovering patients (standard deviation, 8.8) (6), and thus a standard deviation of 6 is expected. Based on a two-sided significance level of 0.05 and a power of 0.9 on Student's t -test, a sample size of 39 per group is needed.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…Using the minimal clinically important difference (MCID) as a reference, the mean difference between the patients in the RT and control groups with respect to the FMA upper-limb score is expected to be 4.25 points (30). Given that the subjects in this study will be chronic patients, the deviation is expected to be smaller than that in the pilot study conducted in recovering patients (standard deviation, 8.8) (6), and thus a standard deviation of 6 is expected. Based on a two-sided significance level of 0.05 and a power of 0.9 on Student's t -test, a sample size of 39 per group is needed.…”
Section: Methodsmentioning
confidence: 87%
“…Hardly any of this research was conducted in East Asia, and thus our study would also be novel in this respect. The robot used in this study, ReoGo-J, is the successor of ReoGo, which was shown to be effective during stroke recovery (6). This study would be the first randomized controlled trial using this new robotic system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations